Enhanced Recovery After Surgery Evidence-Based Practice Perioperative Guideline Implementation for Hepatectomy - Petraitis, Camille (My University, 2018)
Liver cancer is the 10th most common cancer in the United States and the fifth most common cause of cancer-related deaths. Partial hepatectomy continues to remain the most frequently used curative treatment for liver cancer. The Enhanced Recovery After Surgery (ERAS) protocol is a standardized, interdisciplinary, coordinated perioperative care plan that integrates evidence-based interventions to improve surgical outcomes through minimizing the metabolic stress response. Variation in surgical care for hepatectomy can be reduced through ERAS guideline implementation that ultimately leads to improvement in postoperative outcomes. The primary purpose of this project was to implement and evaluate compliance of the ERAS guideline for the three phases of perioperative care in patients undergoing hepatectomy. Secondary aims were to evaluate morbidity, hospital length of stay (HLOS), readmission within 30 days, and 30-day mortality. The ERAS protocol was implemented and data was collected from September 14, 2017 to November 24, 2017. A total of 20 patients were included in this project. The guideline was effectively implemented with a mean overall compliance of 77.7%. Secondary aims showed favorable outcomes when compared with other studies within this institution and will be further discussed within this paper.
Keywords: Enhanced Recovery After Surgery; ERAS; Hepatectomy